IP, R.I.P. - Andrew Gilden (Washington University Law Review, 2017)
Death is an inevitably disruptive event. When a famous artist or public figure dies, the fallout can be particularly complex and contentious. An artist’s surviving family and close friends frequently seek privacy and solitude as they process a deeply personal loss, while millions of fans, by contrast, seek to widely share, rework, and celebrate the decedent’s archive of work. When these very different mourning processes intersect, intellectual property laws play a pivotal role in deciding how an artist is mourned, commemorated, and remembered. This Article reexamines the interests of an artist’s families, friends, and other heirs (IP estates) within the IP system. Previous scholarship has been nearly uniformly critical of IP estates: IP estates “jealously guard” their ancestor’s legacy, “sit back and collect rent,” and put a “stranglehold” on the public domain. This Article, by contrast, reveals a more diverse and sympathetic set of motivations. Although IP estates do often try to restrict fair use and free speech, they also seek to vindicate interests otherwise celebrated in our legal culture: remedying exploitation, protecting family privacy, and maintaining the dignity of the deceased. For the families and friends of individuals in creative fields, IP can serve as a valuable tool in managing the messy tasks of mourning and moving forward. This Article excavates the role of IP in mediating the diverse interests of families and fans as they process the death of an artist. Even if the conduct of IP estates can be highly questionable from a social welfare perspective, recognizing the interests that animate their disputes nonetheless can lead to (1) greater common ground among the various stakeholders negotiating an artist’s cultural legacy and (2) improved use of estate planning to reduce the likelihood of conflict.
Keywords: IP Estates; postmortem rights; parallel mourning; artist; legacy; life-plus-70